PREVALENCE OF METABOLIC SYNDROME AND COMORBID CONDITIONS IN INMATES OF OLD AGE HOMES - N., Sathyanarayana Rao K.; K., Subbalakshmi N. (Journal of Health and Allied Sciences NU, 2012)
Introduction: It is imperative that efforts are to be made to recognize individuals with metabolic syndrome from different sets of population so that they may be identified for intensive risk factor management to reduce cardiovascular risk. We evaluated the incidence and associated factors of metabolic syndrome in inmates of old age homes.Methods: This study involved 189 subjects aged between 55-75 years of either sex housed in old age homes. In every subject waist circumference, blood pressure, fasting blood sugar and plasma lipids were measured. Ongoing treatments were taken into account. Patients with metabolic syndrome were identified using IDF-2005 definition. Data analysis was done by Chi -square test. p value less than 0.05 was taken as significant.Result: Metabolic syndrome was found in 57.67% of study subjects. Prevalence of metabolic syndrome was higher in 55 - 60 years age group (x2 =17.06, p < 0.01) and in females (x2 = 4.33, p < 0.05). Disease load of dyslipidemia, diabetes mellitus and hypertension was higher in metabolic syndrome group compared to non-metabolic syndrome group (x2 = 11.40, p<0.001; x2 = 47.90, p<0.0001; x2 = 4.72, p<0.05 respectively). In patients receiving treatment for diabetes and hypertension, frequency of subjects with hyperglycemia and high blood pressure was higher in metabolic syndrome group compared to non-metabolic syndrome group (x2 = 10.69, p<0.01; x2 = 4.46, p<0.05 respectively).Conclusion: In this population it is found that, 55-60 years age group and females are at greater risk for metabolic syndrome. Subjects with metabolic syndrome are resistant to anti-diabetic and antihypertensive treatment.
Keywords: metabolic syndrome; hyperglycemia; high blood pressure; dyslipidemia